Juvenile Rheumatoid Arthritis - S. Zulkifli; Maimunah Affandi; Bambang Madiono (Indonesian Pediatric Society, 1974)
Juvenile Rheumatoid Arthritis (JRA) or usually also called Still's disease, is a chronic disease occurring in children with the clinical signs and symptoms of joint involvement and systemic manifestation. It has many similarities with adult rheumatoid type, but also distinct differences.